The effect of chlorpyrifos on the aorta - Abdul Razak, Redzuan Nul Hakim; Buyong, Zunariah; Abdullah, Nor Zamzila; A. Talib, Norlelawati (IIUM Press, International Islamic University Malaysia, 2017)
Atherosclerosis is defined as a slow process of inflammation in medium-sized and large arteries fuelled by deposition of lipid. Classified as one of the major non communicable disease, it is accounted for the health burdens facing by many countries. Chlorpyrifos (CPF) is an organophosphorous insecticide that possesses various human systemic toxicities. The present study is therefore designed to demonstrate the atherosclerosis development in rats’ aorta following exposure to CPF. By using powerful tools such as scanning electron microscope and transmission electron microscope, we attempt to visualize ultrastructural alterations of intima layer covering advanced atherosclerotic plaque. Eighteen male Sprague–Dawley rats weighing 150-200 g were grouped into CPF exposed, vehicle exposed and control group. CPF exposed rats received subcutaneous injection of 18 mg/kg chlorpyrifos dissolved in vehicle with a volume of 0.7 ml/kg body weight while vehicle rats administered with vehicle containing 3% Dimethyl sulphoxide and 97% v/v soy oil. The rats were injected intermittently for 6 months. The rats were sacrificed at the end of 6 months of study and the aortic arch tissue was processed for electron microscopy. On observation, there were disruptions of the intimal layer of the CPF exposed rat aorta. Numerous notable endothelial gaps between endothelial cells were identified. The endothelial cells also were irregularly oriented and morphologically changed. Several areas of deendothelialization were noticed. There was no obvious ultrastructural change in the aorta of the rats fed with vehicle. As for transmission electron photomicrograph, foam cells and calcium crystals were found in CPF exposed rat aorta. No foam cell and calcium crystal were found in rats’ aorta exposed to vehicle and without treatment. Histological staining with toluidine blue able to identify several areas of intimal protrusions and elastic fibers disorientation in CPF exposed rat aorta. In conclusion, it is likely that prolonged CPF administration caused vascular wall damage and may be one of the mechanisms involved in CPF-induced atherosclerosis